Handbook of school-based interventions : resolving student problems and promoting healthy educational environments - Cohen, Jeffrey J.; Fish, Marian C. (San Francisco : Jossey-Bass Publishers, 1993)
This comprehensive guide describes practical interventions for virtually every major behavioral problem that students may exhibit from kindergarten to grade 12. It focuses on promoting a healthy and social school environment in which all children can learn and grow.
Includes bibliographical references and indexes.
Keywords: School psychology -- Handbooks, manuals, etc; School social work -- Handbooks, manuals, etc; Problem children -- Education -- Handbooks, manuals, etc; Classroom management -- Handbooks, manuals, etc